CVD diamond coated silicon nitride self-mated systems : tribological behaviour under high loads - Abreu, C. S. (2006)
Friction and wear behaviour of self-mated chemical vapour deposited (CVD) diamond ﬁlms coating silicon nitride ceramics (Si3N4) were investigated in ambient atmosphere. The tribological tests were conducted in a reciprocal motion ball-on-ﬂat type tribometer under applied normal loads up to 80 N (~10 GPa). Several characterisation techniques - including scanning electron microscopy (SEM), atomic force microscopy (AFM) and micro-Raman studies - were used in order to assess the quality, stress state and wear resistance of the coatings. In addition, a novel method is presented to estimate the wear coefficient of the diamond coated ﬂat specimens from AFM and optical microscopy (OM) observations of the wear tracks.